EFFECTIVE WAYS OF USING PICTURES IN TEACHING GRAMMAR - Oqboyeva Shahnoza Abdmalik Qizi,; Xujamurodova Sarvinoz G’anisher Qizi, (Ustozlar uchun, 2025)
The use of visual aids, particularly pictures, has become a powerful tool in teaching grammar, enhancing student engagement and comprehension. This study explores effective strategies for integrating pictures into grammar instruction, focusing on their impact on learner motivation, retention, and understanding of complex grammatical structures. Through a mixed-methods approach, including classroom observations and student feedback, the research identifies key techniques such as contextual visualization, picture-based storytelling, and interactive grammar games. Results indicate that pictures significantly improve students’ ability to grasp abstract grammar concepts and sustain their interest in learning. The findings suggest that educators can optimize grammar instruction by strategically incorporating visuals tailored to learners’ needs and proficiency levels.